Using policy network analysis to understand ideological convergence and change in educational subsystems - Galey-Horn, Sarah; Ferrare, Joseph J. (Education policy analysis archives, 2020)
In recent years, education policy scholars have begun to utilize social network concepts and methods to describe contemporary policy changes across P-16 levels. While many insights have emerged from this growing literature base, we argue that a more formal network approach rooted in policy network analysis (PNA) is needed to fulfill its conceptual and analytical ambitions. Policy network analysis integrates concepts from social network analysis with theoretical assumptions developed in the field of political science. Toward this end, we first argue that a more rigorous treatment of policy beliefs is needed to analyze the impact of ideas on the policy agenda. Existing literature on the ideological dimensions of market-based reform movements tends to define them largely within the bounds of neo-liberalism and thus far has failed to systematically explain how policy beliefs emerge and converge in this context. Second, we contend that previous work has generally lacked theoretical grounding in formal policy network analysis (PNA). Although there are clear links between the concepts and findings in traditional PNA literature and educational research – particularly the use of networked governance as a concept for understanding the interconnectedness of educational reform networks – a more diligent application of PNA theory and methods would enable educational policy scholars to gain deeper insights into the explanatory processes of policy change. We pay particular attention to the usefulness of these approaches for examining two-mode network data and for modeling ideological policy change.